Temporal changes of the respiratory microbiota as cats transition from health to experimental acute and chronic allergic asthma - Vientós-Plotts, Aida I.; Ericsson, Aaron C.; McAdams, Zachary L.; Rindt, Hansjorg; Reinero, Carol R. (Frontiers in Veterinary Science, 2022)
In humans, deviation from a core airway microbiota may predispose to development, exacerbation, or progression of asthma. We proposed to describe microbiota changes in upper and lower airways, and rectal swabs of cats after experimentally induced asthma, in acute (6 weeks) and chronic (36 weeks) stages. We hypothesized that asthma induction would decrease richness and diversity and alter microbiota composition and structure in the lower airways, without significantly impacting other sites. After asthma induction, richness decreased in rectal (p = 0.014) and lower airway (p = 0.016) samples. β diversity was significantly different between health and chronic asthma in all sites, and between all time points for lower airways. In healthy lower airways Pseudomonadaceae comprised 80.4 ± 1.3% whereas Sphingobacteriaceae and Xanthobacteraceae predominated (52.4 ± 2.2% and 33.5 ± 2.1% respectively), and Pseudomonadaceae was absent, in 6/8 cats with chronic asthma. This study provides evidence that asthma leads to dysbiosis in the airways and distant sites.